Evaluating the potential of non-pathogenic Magnaporthaceae species for the control of take-all disease in wheat - Chancellor, Tania (2022)
Take-all disease, caused by the soil-borne ascomycete fungus Gaeumannomyces tritici, is one of the most important root diseases of wheat in the UK and worldwide. The fungus invades the roots and destroys the vascular tissue, hindering the uptake of water and nutrients from the soil. Current control methods include crop rotation, later sowing of crops at risk and the use of partially effective fungicide seed dressings. Closely related species in the Magnaporthaceae family, such as Gaeumannomyces hyphopodioides, occur naturally in arable and grassland soils and have considerable potential to suppress take-all disease. In vitro assays revealed that the direct interaction between G. tritici and G. hyphopodioides is unlikely to play a significant role in take-all control. Co-inoculation bioassays demonstrated that effective take-all control is achieved when G. hyphopodioides colonises the root system before G. tritici. Detailed microscopy analyses revealed that G. hyphopodioides produces chlamydospore-like structures in the root cortex, which could also play a role in the infection cycle. Furthermore, the analyses confirmed previous findings that G. hyphopodioides induces physical plant defence responses such as cell-wall lignification. A dual RNA sequencing experiment of G. tritici infected and G. hyphopodioides colonised roots further highlighted this defence induction and revealed extensive transcriptional reprogramming in wheat following G. hyphopodioides colonisation. Taken together, these findings indicate that induced plant resistance is responsible for take-all control by G. hyphopodioides. Despite the clear upregulation of several defence pathways, plant bioassays revealed that G. hyphopodioides colonisation alone does not adversely affect wheat health. Finally, an improved protocol for virus-induced gene silencing (VIGS) in wheat roots was developed, which could facilitate the functional validation of candidate G. tritici resistance/susceptibility genes in wheat. This PhD project provides novel information regarding wheat responses to G. hyphopodioides and G. tritici infection, and provides vital data which could inform future biocontrol strategies against take-all disease in wheat.